Middle East respiratory syndrome coronavirus (MERS‐CoV) infection: Analyses of risk factors and literature review of knowledge, attitude and practices. (28th April 2022) - Rahman, Arifur; Sarkar, Atanu
Abstract: The study aimed to explore the risk factors for MERS‐CoV infection and systematic review of knowledge, attitudes and practices (KAP) with regard to MERS‐CoV among the health care workers (HCWs) and the general population. The World Health Organization's MERS‐CoV line list (January 2013–January 2020) of the Kingdom of Saudi Arabia (KSA) was analysed. A Poisson regression model was used to calculate the univariate relative risk of outcomes to each potential risk factor, p ‐values and 95% confidence intervals. An electronic literature search was conducted to assess knowledge, attitudes and practices of the HCWs and general population of the KSA, with regards to transmission of the infection, risk factors and preventative measures. The line list analysis shows that age, gender, comorbidity, exposure to camels and camel milk consumption were associated with an increased risk of fatality; however, year‐wise analysis did not show any decline. Over the years, the mean durations between the symptom onset and hospitalization; the hospitalization and laboratory confirmation have reduced. The review of literature shows that the health care workers and the general population had inadequate knowledge about MERS‐CoV, lacked motivation and were disconnected from the health authorities. The WHO line list provides information on risk factors for MERS‐CoV, KAP analysis helps to know the potential underlying factors. The literature review shows that continuous education for HCWs and increasing public awareness can help effectively manage future MERS‐CoV.